Method for degrading organic pollutants in water body by using modified goethite reinforced ferrate
Through metal doping and calcining treatment of modified goiterite, the problems of low activation efficiency of high ferrate and poor stability of goiterite in the prior art are solved, and efficient degradation of organic pollutants in water bodies is achieved, with excellent catalytic performance and stability.
Patent Information
- Application Number
- CN202411801576.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively activate ferrate (Fe(VI)), resulting in low efficiency in degrading organic pollutants in water, and conventional goiterite has problems such as poor stability and low conversion efficiency.
Modified goite is prepared by metal doping and calcining treatment, and modified goite is added to the degradation system constructed by ferrate to improve the activity and degradation efficiency of ferrate.
It significantly improves the catalytic capacity and stability of modified goiterite, enhances the activity of ferrate, and achieves efficient degradation of organic pollutants in water, with strong degradation selectivity, high efficiency, low dosage and no secondary pollution.
Smart Images

Figure CN119503999A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material science and water pollution control, and relates to a method for utilizing modified goethite to strengthen ferrate to degrade organic pollutants in water. Background Art
[0002] Ferrate (Fe(VI)) is an environmentally friendly oxidant, disinfectant and flocculant with excellent removal effect on organic pollutants. It also produces Fe(III) as a reaction byproduct. It is worth noting that in a neutral or alkaline environment, Fe(III) produces non-toxic and easily precipitated Fe(OH)3, which can be easily removed and is not likely to cause secondary pollution to the environment. Therefore, advanced oxidation technologies based on ferrate (Fe(VI)) can be used to degrade organic pollutants in water and have received great attention. However, Fe(VI) itself selectively degrades electron-rich organic pollutants (such as aniline, phenol and amine), and its oxidation characteristics largely depend on pH and the initial concentration of Fe(VI). In addition, Fe(VI) is unstable in water and easily self-decays. The relatively high and rapid self-decomposition rate may reduce the utilization efficiency of Fe(VI) in practical applications (less than 10%). Therefore, it is necessary to explore effective methods to accelerate the removal of organic pollutants by Fe(VI).
[0003] Currently, there are many methods to activate Fe(VI) to produce a large amount of Fe(IV) / Fe(V), including metal ions, colloidal manganese dioxide, reducing agents (such as sulfite, hydroxylamine and hydrogen peroxide), nano zero-valent iron and biochar. However, these homogeneous reducing agents have potential environmental risks. Nano zero-valent iron also has the defects of unstable chemical properties and biochar has low activity, which makes them difficult to be widely used for Fe(VI) activation, thus limiting the practical application of ferrate (Fe(VI))-based advanced oxidation technology in the degradation of organic pollutants in water. Compared with the above homogeneous reducing agents, using goethite as a heterogeneous catalyst to enhance the activity of ferrate has application advantages. Goethite (α-FeOOH) has the advantages of being abundant on the surface, widely available, low cost, high specific surface area, rich active sites and simple preparation. Its stable crystal structure can resist hydrolysis and dissolution and will not cause secondary pollution to the environment. However, conventional goethite has problems such as poor stability of Fe(III) / Fe(II) and low conversion efficiency, which makes it difficult to effectively activate ferrate (Fe(VI)). As a result, advanced oxidation technology based on ferrate (Fe(VI)) is difficult to quickly degrade organic pollutants in water. Therefore, how to obtain a catalyst with good catalytic ability and good stability is of great significance for reducing the dosage of ferrate (Fe(VI)) and achieving efficient degradation of organic pollutants in water. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for degrading organic pollutants in water by using modified goethite to enhance ferrate, which has high degradation efficiency, good removal effect, small amount of catalyst and oxidant, and is green and environmentally friendly.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for utilizing modified goethite to strengthen ferrate to degrade organic pollutants in water, wherein the modified goethite is added to a degradation system constructed by ferrate to degrade the organic pollutants in the water; the modified goethite is prepared by calcining metal-doped goethite as a raw material; the doped metal in the metal-doped goethite is cobalt and / or copper.
[0006] The above method is further improved, and the preparation method of the modified goethite comprises the following steps: S1, mixing a doped metal salt with an iron salt to react to obtain metal-doped goethite; S2. calcining the metal-doped goethite obtained in step S1 to obtain modified goethite.
[0007] The above method is further improved, in step S1, the mass of the doped metal salt is 0.1% to 5% of the mass of the iron salt; the doped metal salt is cobalt nitrate and / or copper nitrate; and the iron salt is iron nitrate.
[0008] The above method is further improved, in step S1, the mass of the doped metal salt is 0.8% to 5% of the mass of the iron salt.
[0009] The above method is further improved in that the calcination is carried out in a reducing atmosphere; the reducing atmosphere is hydrogen or a mixed atmosphere of hydrogen and argon; the volume fraction of hydrogen in the mixed atmosphere is 5% to 15%.
[0010] The above method is further improved in that the calcination temperature is 150°C to 250°C; and the calcination time is 2h to 4h.
[0011] The above method is further improved in that the calcination temperature is 180°C to 220°C.
[0012] The above method is further improved by adding modified goethite to the degradation system constructed by ferrate to degrade organic pollutants in the water body, including the following steps: mixing modified goethite, ferrate and organic pollutant wastewater for oxidative degradation reaction to complete the degradation of organic pollutants in the wastewater.
[0013] The above method is further improved, wherein the amount of modified goethite added is 0.1 g to 0.5 g per liter of the organic pollutant wastewater; the amount of ferrate added is 0.05 mmol to 0.5 mmol per liter of the organic pollutant wastewater.
[0014] The above method is further improved, wherein the organic pollutants in the organic pollutant wastewater are at least one of 2,4-dichlorophenol, sulfamethoxazole, oxytetracycline, tetracycline, phenol and bisphenol A; and the initial concentration of the organic pollutants in the organic pollutant wastewater is 10 μmol / L to 30 μmol / L.
[0015] The above method is further improved, wherein the oxidative degradation reaction process also includes: adding borax-boric acid buffer solution to control the initial pH value of the system to 9.0±0.1; the pH value of the borax-boric acid buffer solution is 9.0; the temperature of the oxidative degradation reaction is 20°C to 40°C, and the oxidative degradation reaction is carried out under stirring conditions; the stirring speed is 100 rpm to 200 rpm; and the time of the oxidative degradation reaction is 30 min to 150 min.
[0016] The above method is further improved in that inorganic anions are also added to the organic pollutant wastewater.
[0017] Compared with the prior art, the advantages of the present invention are: (1) In view of the shortcomings of goethite, such as poor stability of Fe(III) / Fe(II), low conversion efficiency, low content of oxygen vacancies and surface active Fe(II) sites, and the defects of goethite that it is difficult to effectively activate Fe(VI) and remove organic pollutants in water efficiently, the present invention creatively proposes a method for using modified goethite to enhance the degradation of organic pollutants in water by ferrate, wherein modified goethite is added to the degradation system constructed by ferrate, wherein the modified goethite is prepared by calcining metal-doped goethite. On the one hand, through metal doping and calcination, The chemical environment of iron can be changed and a second atom (cobalt and / or copper) can be introduced into iron-containing materials such as goethite, thereby changing the electronic structure of goethite and forming more active surface sites, which can improve the adsorption, degradation and catalytic properties of goethite. On the other hand, the oxygen vacancies and surface active Fe(II) sites on goethite can be significantly increased by metal doping and calcination. By introducing a large number of oxygen vacancies on goethite, favorable electron transfer to low-coordinated Fe(III) sites can be promoted to form Fe(II), thereby strengthening advanced oxidation reactions and occupying O after the oxygen vacancies are generated. The surrounding electrons of the 2p orbital are delocalized to form a higher local electron density, which further promotes interfacial charge transfer and conductivity. In addition, the modified goethite used has oxygen vacancies rich in local electrons, which can significantly enhance the adsorption and activation of molecular oxygen. At the same time, by increasing the content of oxygen vacancies and surface active Fe(II) sites on the goethite, the content and density of active sites on the modified goethite can be significantly increased, thereby effectively activating ferrate and significantly increasing the yield of active species in the reaction system. It exhibits excellent degradation performance for a variety of organic pollutants, and has a short reaction time, which is very beneficial to the efficient removal of organic pollutants in water bodies. More importantly, compared with conventional goethite, the modified goethite prepared by the present invention exhibits better catalytic ability and stability, and is therefore more beneficial to the efficient removal of organic pollutants in water bodies. In the method of utilizing modified goethite to enhance ferrate degradation of organic pollutants in water bodies of the present invention, ferrate is activated by utilizing modified goethite having abundant oxygen vacancies and surface active Fe(II) sites, which can promote ferrate to rapidly generate a large number of highly active species, thereby being able to construct a catalytic degradation system based on high-valent metals, and being able to achieve efficient degradation of organic pollutants in water bodies with less ferrate usage, being able to efficiently remove a variety of organic pollutants in water bodies, having the advantages of strong degradation selectivity, high degradation efficiency, good removal effect, low usage of catalysts and oxidants, no secondary pollution, and the like, having high use value and good application prospects.
[0018] (2) In the present invention, the mass of the doped metal salt is optimized to be 0.1% to 5% of the mass of the iron salt. By optimizing the metal doping ratio, a modified goethite with excellent performance and stronger stability can be obtained, which can meet different application requirements. In particular, when the doped metal ratio is too high, too much doped metal may destroy the crystal structure of goethite, aggravate the particle agglomeration phenomenon of the calcined product, and reduce the utilization efficiency of the active sites; when the metal doping ratio is too low, too little doped metal has an insignificant modification effect on goethite, and there is still a problem of insufficient number of active sites.
[0019] (3) In the present invention, calcination is carried out in a hydrogen reducing atmosphere. On the one hand, the metal can be prevented from being oxidized. On the other hand, the reducing effect of hydrogen can be used to reduce part of the metal during the calcination process, thereby increasing the oxygen vacancy content. At the same time, calcination in a hydrogen reducing atmosphere is simple to operate, has mild reaction conditions, does not cause side reactions, has low toxicity, and has no irritating odor.
[0020] (4) In the present invention, the calcination temperature is also optimized to 150 ℃ to 250 ℃, and a modified goethite with better performance and more stability can be obtained. For example, compared with the uncalcined goethite, when the calcination temperature is 200 ℃, the degradation rate of the prepared modified goethite is increased by 2.21 times. In particular, when the calcination temperature is too high (such as the calcination temperature is 300 ℃), the crystal structure of the goethite itself may be destroyed, the doped metal may be volatilized or the agglomeration phenomenon may be aggravated, resulting in a poor activation effect on ferrate, thereby reducing the degradation performance of the system; and when the calcination temperature is too low, the generated product may have poor crystallinity, and the doped metal may not react completely with the goethite, which is not conducive to obtaining modified goethite with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0022] Figure 1 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by metal-doped goethite and Fe(VI) at different doping ratios in Example 1 of the present invention.
[0023] Figure 2 This is a fitted kinetic first-order rate diagram of the degradation system constructed by metal-doped goethite and Fe(VI) with different doping ratios in Example 1 of the present invention for sulfamethoxazole.
[0024] Figure 3 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite and Fe(VI) prepared at different calcination temperatures in Example 1 of the present invention.
[0025] Figure 4 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite and Fe(VI) prepared at different calcination temperatures in Example 1 of the present invention for sulfamethoxazole.
[0026] Figure 5 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite with different cobalt doping ratios and Fe(VI) in Example 2 of the present invention.
[0027] Figure 6 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite with different cobalt doping ratios and Fe(VI) in Example 2 of the present invention for sulfamethoxazole in water.
[0028] Figure 7 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite and Fe(VI) under different goethite concentration conditions in Example 3 of the present invention.
[0029] Figure 8 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite and Fe(VI) under different goethite concentration conditions in Example 3 of the present invention for sulfamethoxazole in water.
[0030] Fig. 9 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite with different doped metals and Fe(VI) in Example 4 of the present invention.
[0031] Fig.10 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite with different doped metals and Fe(VI) in Example 4 of the present invention for sulfamethoxazole in water.
[0032] Fig.11 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite and different concentrations of Fe(VI) in Example 5 of the present invention.
[0033] Fig.12 This is a diagram showing the degradation effect of sulfamethoxazole in water under different anion conditions by the system constructed by modified goethite and Fe(VI) in Example 6 of the present invention.
[0034] Fig.13 This is a diagram showing the degradation effect of sulfamethoxazole in water under different pH conditions using the degradation system constructed by modified goethite and Fe(VI) in Example 7 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0036] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0037] Example 1 A method for utilizing modified goethite to enhance ferrate to degrade organic pollutants in water, specifically adding modified goethite to a degradation system constructed by ferrate to degrade sulfamethoxazole in water, comprising the following steps: 100 mL of 25.0 μM sulfamethoxazole solution was taken into a 250 mL conical flask, and the pH was controlled at 9.0±0.1 using borax-boric acid buffer solution with a pH of 9.0. At the same time, modified goethite and potassium ferrate Fe(VI) were added for oxidative degradation reaction. The dosages of modified goethite and Fe(VI) in the reaction system were 0.2 g / L and 0.2 mmol / L, respectively. The reaction was carried out in a water bath shaker with a rotation speed of 150 rpm, a temperature of 30°C, and a reaction time of 30 min to complete the degradation of sulfamethoxazole in the water.
[0038] In this embodiment, the modified goethite used is prepared by calcining metal-doped goethite as a raw material, wherein the doped metal in the metal-doped goethite used is cobalt, copper or aluminum.
[0039] In this embodiment, the preparation method of modified goethite prepared under different doping ratios and different doping metal conditions comprises the following steps: (1) Metal-doped goethite with different doping ratios and different doping metals was prepared by co-precipitation method.
[0040] (1.1) Prepare mixed solutions containing iron nitrate and doping metals according to different doping ratios, such as a mixed solution of aluminum nitrate and iron nitrate, a mixed solution of cobalt nitrate and iron nitrate, and a mixed solution of copper nitrate and iron nitrate. These solutions will be used as precursors for subsequent precipitation reactions.
[0041] In this step, in the mixed solutions with different doping ratios, the mass of the doped metal salt is 0.1%, 0.5%, 1%, and 5% of the mass of the iron salt.
[0042] (1.2) Slowly add an appropriate amount of the above mixed solution to a high concentration of sodium hydroxide solution. During the addition process, continue stirring to ensure sufficient mixing. After complete mixing, add an appropriate amount of ultrapure water to dilute. Subsequently, seal the reaction vessel with plastic wrap, place it in a water bath heating pot, and heat it at 70°C for 48 hours to ensure that the chemical reaction is fully carried out. After the reaction is completed, the precipitate in the lower layer is washed with ultrapure water until neutral, and the solution is centrifuged to obtain a precipitate. Subsequently, filter it and dry it in a vacuum drying oven at 60°C for 12 hours. The dried solid material is ground and screened through a 100-mesh sieve to ensure that the particle size is uniform, and goethite with different doping ratios and different doped metals is obtained. Finally, the obtained metal-doped goethite powder with different doping ratios and different doped metals is collected in a centrifuge tube for subsequent use.
[0043] (2) Metal-doped goethite powders with different doping ratios and different doping metals were calcined under a reducing atmosphere to prepare modified goethite rich in oxygen vacancies and active Fe(II) sites. The detailed method is as follows: First, 1 g of metal-doped goethite powder with different doping ratios and different doped metals was weighed and added to the magnetic boat respectively. Then, the magnetic boat was moved to a tube furnace and carried out under a H2 / Ar atmosphere (the volume ratio of hydrogen to argon in the atmosphere was 1:9) with a gas flow rate of 50 mL / min. Before starting heating, the mixed gas was introduced for 10-15 minutes to ensure that the oxygen in the tube furnace was completely removed. Subsequently, the temperature of the tube furnace was raised to 200°C or 300°C at a heating rate of 5°C / min and maintained at this temperature for 2 hours to ensure that the reaction was fully carried out. After completing the heat treatment process, the tube furnace was turned off and allowed to cool naturally to room temperature. Then, the treated goethite powder was carefully taken out and transferred to a centrifuge tube to obtain modified goethite with different doping ratios and different doped metals.
[0044] In this embodiment, the undoped goethite used is prepared by a hydrolysis method, which includes the following steps: (1) Under continuous stirring, adjust the pH of a certain concentration of ferric nitrate solution to 11.0 using sodium hydroxide solution.
[0045] (2) Aging the above solution at 80°C for 6 h.
[0046] (3) Wash with deionized water until neutral and collect the precipitate.
[0047] (4) Dry the precipitate and grind it to obtain goethite.
[0048] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Figure 1 and Figure 2 shown.
[0049] Figure 1 This is a diagram showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by metal-doped goethite and Fe(VI) at different doping ratios in Example 1 of the present invention. Figure 1 Among them, FeOOH / Fe(VI) refers to the degradation system constructed by undoped goethite and potassium permanganate; Co-FeOOH / Fe(VI) refers to the degradation system constructed by metal cobalt doped goethite and potassium permanganate; Al-FeOOH / Fe(VI) refers to the degradation system constructed by metal aluminum doped goethite and potassium permanganate. At the same time, Figure 1 In the above, 0.1% doping, 0.5% doping, 1% doping, and 5% doping refer to the preparation method of metal-doped goethite, in which the mass of the doped metal salt is 0.1%, 0.5%, 1%, and 5% of the mass of the iron salt, respectively. Figure 1 As shown, the results showed that in the experimental groups of metal cobalt-doped goethite (Co-FeOOH) with different doping ratios (0.1%, 0.5%, 1%, and 5%), the degradation rates of sulfamethoxazole in water by the degradation system constructed by metal cobalt-doped goethite (Co-FeOOH) and Fe(VI) were 17.11%, 13.87%, 22.82% and 20.71%, respectively. In the experimental groups of aluminum-doped goethite (Al-FeOOH) with different doping ratios (0.1%, 0.5%, 1%, and 5%), the degradation rates of sulfamethoxazole in water by the degradation system constructed by aluminum-doped goethite (Al-FeOOH) and Fe(VI) were 13.71%, 13.42%, 10.64% and 8.71%, respectively. By comparison, it can be seen that the activity of Co doping in goethite is significantly better than that of Al doping, especially the degradation rate of goethite doped with metal cobalt (Co-FeOOH) with a doping ratio of 1% reached the optimal 22.82%, which is 12.18% and 9.1% higher than the degradation rates of metal cobalt doped with goethite (Al-FeOOH) and undoped goethite (FeOOH) under the same conditions, respectively.
[0050] Figure 2 This is a fitted kinetic first-order rate diagram of the degradation system constructed by metal-doped goethite and Fe(VI) with different doping ratios in Example 1 of the present invention for sulfamethoxazole in water. Figure 2In the figure, FeOOH is undoped goethite; 0.1%Al, 0.5%Al, 1%Al, 5%Al correspond to metal aluminum-doped goethite (Al-FeOOH) with doping ratios of 0.1%, 0.5%, 1%, and 5%; 0.1%Co, 0.5%Co, 1%Co, 5%Co correspond to metal cobalt-doped goethite (Co-FeOOH) with doping ratios of 0.1%, 0.5%, 1%, and 5%. Figure 2 As shown in the data, the degradation rate of sulfamethoxazole in water by the degradation system constructed by 1% cobalt-doped goethite (Co-FeOOH) and Fe(VI) is 1.44 times that of the degradation system constructed by undoped goethite (FeOOH) and Fe(VI), while the degradation rate of sulfamethoxazole in water by the degradation system constructed by aluminum-doped goethite (Al-FeOOH) and Fe(VI) is generally lower than that of the FeOOH / Fe(VI) system.
[0051] Depend on Figure 1 and Figure 2 It can be seen from the results in that in the present invention, when the mass of the doped metal salt is 0.1% to 5% of the mass of the iron salt, the corresponding metal cobalt-doped goethite is more suitable for preparing modified goethite.
[0052] In this example, the degradation performance of sulfamethoxazole by the degradation system constructed by different modified goethites prepared under different calcination conditions and Fe(VI) was also investigated. Figure 3 and Figure 4 shown. Figure 3 and Figure 4 In the formula, 200°C FeOOH refers to a modified goethite prepared by calcining undoped goethite at 200°C, and 300°C FeOOH refers to a modified goethite prepared by calcining undoped goethite at 300°C; 200°C Co-FeOOH refers to a modified goethite prepared by calcining cobalt-doped goethite at 200°C, and 300°C Co-FeOOH refers to a modified goethite prepared by calcining cobalt-doped goethite at 300°C, wherein the mass of the doped metal salt in the preparation method of cobalt-doped goethite is 1% of the mass of the iron salt; 200°C Al-FeOOH refers to a modified goethite prepared by calcining aluminum-doped goethite at 200°C, and 300°C Al-FeOOH refers to modified goethite prepared by calcining metal aluminum-doped goethite at 300°C, wherein the mass of the doped metal salt is 1% of the mass of the iron salt in the preparation method of the metal aluminum-doped goethite. Figure 3 The degradation effect of modified goethite prepared at different calcination temperatures in Example 1 of the present invention and the degradation system constructed by Fe(VI) on sulfamethoxazole in water is shown in FIG. Figure 3 It can be seen that the degradation rates of modified goethite (200℃ Co-FeOOH, 200℃ Al-FeOOH, 200℃ FeOOH) prepared by calcining different metal-doped goethite (Co-FeOOH, Al-FeOOH, FeOOH) at 200℃ and the degradation system constructed with ferrate for sulfamethoxazole in water are 39.34%, 16.57%, and 29.73%, respectively. Compared with the corresponding uncalcined metal-doped goethite (Co-FeOOH, Al-FeOOH, FeOOH), their degradation rates are increased by 16.52%, 5.93%, and 16.01%, respectively. Figure 1 The results show that the degradation rates of sulfamethoxazole in water by the degradation system constructed by uncalcined metal-doped goethite (Co-FeOOH, Al-FeOOH, FeOOH) and ferrate are 22.82%, 10.64%, and 13.72%, respectively. Figure 3 It can be seen that the degradation rate of sulfamethoxazole in water by the modified goethite (300℃ Co-FeOOH, 300℃ Al-FeOOH, 300℃ FeOOH) prepared by calcining different metal-doped goethites (Co-FeOOH, Al-FeOOH, FeOOH) at 300℃ and the degradation system constructed with ferrate decreased to 11.01%, 4.04%, and 4.36%. Compared with the corresponding uncalcined metal-doped goethites (Co-FeOOH, Al-FeOOH, FeOOH), their degradation rates decreased by 11.81%, 6.60%, and 9.36%, respectively.
[0053] Figure 4 The first-order rate diagram of the degradation system constructed by modified goethite and Fe(VI) prepared at different calcination temperatures in Example 1 of the present invention for sulfamethoxazole. Figure 4 As shown in the figure, the degradation rate of sulfamethoxazole in water by the degradation system constructed by modified goethite (200℃ Co-FeOOH) and ferrate is 1.42 times that of modified goethite (200℃ FeOOH) and 2.21 times that of uncalcined metal-doped goethite (Co-FeOOH). However, for modified goethite (200℃ Al-FeOOH), since it is difficult to increase the oxygen vacancy content in metal-doped goethite (Al-FeOOH) in a hydrogen reducing atmosphere, the prepared modified goethite (200℃ Al-FeOOH) has a limited effect on the degradation rate of sulfamethoxazole in water, and is even inferior to that of modified goethite (200℃ FeOOH). At the same time, Figure 4It can be seen that the degradation rate of the degradation system constructed by modified goethite calcined at 300°C is also significantly reduced. The reason may be that when the calcination temperature is too high, the crystal structure of the goethite itself may be destroyed, causing the volatilization loss of the doped metal or aggravating the agglomeration phenomenon, resulting in its activation effect on ferrate becoming worse, thereby reducing the degradation performance of the system.
[0054] Based on the above experimental results, it can be concluded that the modified goethite prepared by calcining goethite with a doping ratio of 0.1% to 5% as the raw material at 150 ℃ to 250 ℃ shows abundant oxygen vacancies and active Fe(II) sites. In particular, the modified goethite prepared by calcining goethite with a doping ratio of 1% as the raw material at 200 ℃ shows the best performance, and thus can show the best degradation rate and degradation rate in synergy with Fe(VI).
[0055] Example 2 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically investigating the degradation effect of a degradation system constructed by using goethite doped with metal cobalt in different doping ratios (0.1%, 0.5%, 1%, 5%) as a raw material and calcined at 200°C and Fe(VI) on sulfamethoxazole in water, comprising the following steps: Four different doping ratios (0.1%, 0.5%, 1%, 5%) of metal cobalt-doped goethite without calcination, and modified goethite prepared by calcining at 200°C with four different doping ratios (0.1%, 0.5%, 1%, 5%) of metal cobalt-doped goethite as raw materials, were selected as the research objects. These materials were added to the Fe(VI) system, and their effects on the degradation effect of sulfamethoxazole were studied under the same experimental conditions. The experimental reaction time was set to 60 minutes, and the other conditions were the same as those in Example 1. Samples were taken at the time points of (0, 15, 30, 45, 60 minutes), and the residual concentration of sulfamethoxazole at each time point was determined by liquid chromatography.
[0056] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Figure 5 and Figure 6 shown. Figure 5 and Figure 6Here, uncalcined refers to metallic cobalt-doped goethite with different cobalt doping ratios (0.1%, 0.5%, 1%, 5%) that has not been calcined; 200°C calcined refers to modified goethite prepared by calcining metallic cobalt-doped goethite with different cobalt doping ratios (0.1%, 0.5%, 1%, 5%) at 200°C.
[0057] Figure 5 The degradation effect diagram of sulfamethoxazole in water by the degradation system constructed by modified goethite with different cobalt doping ratios and Fe(VI) in Example 2 of the present invention is shown. Figure 5 As shown in the figure, the degradation rates of sulfamethoxazole by metal cobalt-doped goethite with different cobalt doping ratios (0.1%, 0.5%, 1%, 5%) without calcination were 32.38%, 33.93%, 35.06%, and 36.92%, respectively. The degradation rates of sulfamethoxazole by modified goethite rich in oxygen vacancies and active Fe(II) sites prepared by calcining metal cobalt-doped goethite with different cobalt doping ratios (0.1%, 0.5%, 1%, 5%) at 200℃ were significantly increased to 49.49%, 44.39%, 52.92%, and 45.32%, which were 17.11%, 10.46%, 17.86%, and 8.4% higher than those of uncalcined metal cobalt-doped goethite, respectively.
[0058] Figure 6 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite with different cobalt doping ratios and Fe(VI) for sulfamethoxazole in water in Example 2 of the present invention. Figure 6 As shown, compared with the uncalcined metal cobalt-doped goethite (1% Co-FeOOH and 0.1% Co-FeOOH) with a cobalt doping ratio of 1% and 0.1%, the degradation rates of the modified goethite (200℃ 1% Co-FeOOH and 200℃ 0.1% Co-FeOOH) prepared by calcining at 200℃ with metal cobalt-doped goethite (1% Co-FeOOH and 0.1% Co-FeOOH) as raw materials in the present invention were increased by 1.71 times and 1.68 times, respectively, and the degradation rate of the former was 1.12 times that of the latter. In addition, compared with the uncalcined metal cobalt-doped goethite (5% Co-FeOOH and 0.5% Co-FeOOH) with a cobalt doping ratio of 5% and 0.5%, the degradation rates of the modified goethite (200℃ 5% Co-FeOOH and 200℃ 0.5% Co-FeOOH) prepared by calcining at 200℃ with metal cobalt-doped goethite (5% Co-FeOOH and 0.5% Co-FeOOH) as raw materials in the present invention were increased by 1.27 times and 1.35 times, respectively.
[0059] Depend on Figure 5 and Figure 6It can be seen from the results in that in the present invention, when the mass of the doped metal salt is 0.1% to 5% of the mass of the iron salt, the corresponding metal-doped goethite can be used to prepare modified goethite, which can efficiently activate ferrate and promote ferrate to quickly produce a large number of highly active species, thereby constructing a catalytic degradation system based on high-valent metals, and can achieve efficient degradation of organic pollutants in water bodies with less ferrate. In particular, when the mass of the doped metal salt is 0.8% to 5% of the mass of the iron salt, the modified goethite prepared has more excellent performance, can activate ferrate more quickly, and thus can more significantly improve the degradation efficiency of sulfamethoxazole.
[0060] Example 3 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically investigating the degradation effect of a degradation system constructed by modified goethite and Fe(VI) under different goethite concentration conditions on sulfamethoxazole in water, comprising the following steps: 100 mL of a 12.5 μM sulfamethoxazole solution was taken into a 250 mL conical flask, and a borax-boric acid buffer solution with a pH of 9.0 was used to control the pH at 9.0±0.1. At the same time, modified goethite and potassium ferrate (Fe(VI)) prepared by calcining goethite doped with metal cobalt at a doping ratio of 1% as a raw material at 200°C in Example 1 were added to initiate an oxidative degradation reaction, wherein the modified goethite in the reaction system was 200 mg / L, 500 mg / L, 1000 mg / L, and 2000 mg / L, respectively, and the dosage of Fe(VI) was 0.2 mmol / L. The reaction was carried out in a water bath shaker at a speed of 150 rpm, a temperature of 30°C, and a reaction time of 120 min to complete the degradation of sulfamethoxazole in the water.
[0061] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Figure 7 and Figure 8 shown.
[0062] Figure 7 The degradation effect of modified goethite and Fe(VI) on the degradation of sulfamethoxazole in water under different goethite concentration conditions in Example 3 of the present invention is shown in FIG. Figure 7It can be seen that the degradation rates of sulfamethoxazole by modified goethite with four different goethite concentrations (200 mg / L, 500 mg / L, 1000 mg / L, 2000 mg / L) were 85.65%, 85.94%, 68.63%, and 76.30%, respectively. It can be seen that the degradation rates of the experimental groups with the addition concentrations of 200 mg / L and 500 mg / L were close, and significantly higher than those of the experimental groups with the addition concentrations of 1000 mg / L and 2000 mg / L.
[0063] Figure 8 This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite and Fe(VI) under different goethite concentration conditions in Example 3 of the present invention for sulfamethoxazole in water. Figure 8 As shown, when the dosage of modified goethite is 200 mg / L and 500 mg / L, the degradation rate is higher than that of modified goethite with dosage of 1000 mg / L and 2000 mg / L.
[0064] Depend on Figure 7 and Figure 8 The results show that the higher the concentration of modified goethite is, the better it is. Too high a concentration may inhibit the degradation of sulfamethoxazole by potassium ferrate. Therefore, considering the cost and efficiency of the material, in the present invention, when the amount of modified goethite added is 0.1 g to 0.5 g per liter of organic pollutant wastewater, it can effectively activate ferrate and efficiently degrade organic pollutants in water, and significantly reduce the treatment cost.
[0065] Example 4 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically investigating the degradation effect of a degradation system constructed by modified goethite doped with different metals and Fe(VI) on sulfamethoxazole in water, comprising the following steps: 100 mL of a 10.0 μM sulfamethoxazole solution was taken into a 250 mL conical flask, and the pH was controlled at 9.0±0.1 using a borax-boric acid buffer solution with a pH of 9.0. At the same time, modified goethite and potassium ferrate (Fe(VI)) prepared by calcining goethite doped with metal cobalt at a doping ratio of 1% as a raw material at 200° C. in Example 1 were added to initiate an oxidative degradation reaction, wherein the dosages of modified goethite and Fe(VI) in the reaction system were 200 mg / L and 0.2 mmol / L, respectively. The reaction was carried out in a water bath shaker at a speed of 150 rpm, a temperature of 30° C., and a reaction time of 150 min to complete the degradation of sulfamethoxazole in the water.
[0066] In this example, the degradation effect of sulfamethoxazole in water by constructing a degradation system consisting of ferrate alone, modified goethite prepared by calcining undoped goethite at 200°C, modified goethite prepared by calcining goethite with a doping ratio of 1% and 1% of metal copper as a raw material at 200°C, and modified goethite prepared by calcining goethite with a doping ratio of 1% and 1% of metal aluminum as a raw material at 200°C was also investigated, while other conditions were the same.
[0067] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Fig. 9 and Fig.10 shown. Fig. 9 and Fig.10 In the above, Fe(VI) refers to a degradation system constructed by potassium permanganate alone; FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining undoped goethite at 200°C and potassium permanganate; Co-FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining goethite doped with 1% cobalt as a raw material at 200°C and potassium permanganate; Al-FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining goethite doped with 1% aluminum as a raw material at 200°C and potassium permanganate; Cu-FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining goethite doped with 1% copper as a raw material at 200°C and potassium permanganate.
[0068] Fig. 9 This is a graph showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite with different doped metals and Fe(VI) in Example 4 of the present invention. Fig. 9 It can be seen that the degradation rates of sulfamethoxazole in the Co-FeOOH / Fe(VI) system and the Cu-FeOOH / Fe(VI) system reached 100% at 90 minutes. However, the degradation rates of sulfamethoxazole in the Al-FeOOH / Fe(VI) system and the FeOOH / Fe(VI) system were 66.72% and 84.91% respectively at 150 minutes. This indicates that the modified goethite doped with 1% metallic aluminum and the modified goethite without metal doping played a negative role in their respective systems, inhibiting the degradation effect of potassium ferrate on sulfamethoxazole.
[0069] Fig.10This is the fitted kinetic first-order rate diagram of the degradation system constructed by modified goethite with different doped metals and Fe(VI) in Example 4 of the present invention for sulfamethoxazole in water. Fig.10 It can be seen that the degradation rates of the Co-FeOOH / Fe(VI) system and the Cu-FeOOH / Fe(VI) system are both very high, which are 1.28 times and 1.29 times of the undoped FeOOH / Fe(VI) system, respectively. This shows that the modified goethite prepared by calcining at 200°C with metal cobalt-doped goethite and metal copper-doped goethite with a doping ratio of 1% as raw materials shows very excellent performance, and the degradation system constructed by them with potassium permanganate can also significantly improve the degradation efficiency of Fe(VI) for sulfamethoxazole, which can be widely used to degrade organic pollutants in water bodies and promote the effective removal of organic pollutants in water bodies.
[0070] Example 5 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically comparing the performance differences between the Fe(VI) system and the Co-FeOOH / Fe(VI) system in the degradation of sulfamethoxazole under different Fe(VI) concentration conditions, comprising the following steps: 100 mL of a 10.0 μM sulfamethoxazole solution was taken into a 250 mL conical flask, and the pH was controlled at 9.0±0.1 using a borax-boric acid buffer solution with a pH of 9.0. At the same time, modified goethite and potassium ferrate (Fe(VI)) prepared by calcining goethite doped with metal cobalt at a doping ratio of 1% as a raw material at 200° C. in Example 1 were added to initiate an oxidative degradation reaction, wherein the modified goethite in the reaction system was 0.2 g / L, and the dosages of Fe(VI) were 0.01 mmol / L, 0.05 mmol / L, 0.1 mmol / L, and 0.4 mmol / L, respectively. The reaction was carried out in a water bath shaker at a speed of 150 rpm, a temperature of 30° C., and a reaction time of 150 min to complete the degradation of sulfamethoxazole in the water.
[0071] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Fig.11 shown. Fig.11 In the above, Fe(VI) refers to a degradation system constructed by potassium permanganate alone; Co-FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining goethite doped with 1% cobalt as a raw material at 200°C and potassium permanganate.
[0072] Fig.11 This is a graph showing the degradation effect of sulfamethoxazole in water by the degradation system constructed by modified goethite and different concentrations of Fe(VI) in Example 5 of the present invention. Fig.11 It can be seen that the degradation rates of sulfamethoxazole by the Co-FeOOH / Fe(VI) system in the four different concentrations of Fe(VI) experimental groups (0.01 mM, 0.05 mM, 0.1 mM, and 0.4 mM) were 25.36%, 75.64%, 83.33%, and 100%, respectively. The degradation rates of the Fe(VI) system in the same concentration of Fe(VI) experimental groups were 10.54%, 46.76%, 63.62%, and 100%, respectively. In contrast, when the Fe(VI) concentration was 0.01 mM, 0.05 mM, and 0.1 mM, the degradation efficiency of the Co-FeOOH / Fe(VI) system was increased by 14.82%, 28.88%, and 19.71%, respectively, compared with the Fe(VI) system. When the Fe(VI) concentration was 0.4 mM, the Co-FeOOH / Fe(VI) system and the Fe(VI) system both achieved 100% degradation of sulfamethoxazole at the 60-minute time point, but excessive addition of Fe(VI) would easily increase the treatment cost and bring about the risk of secondary pollution. Therefore, the Co-FeOOH / Fe(VI) system had better degradation performance for sulfamethoxazole than the pure Fe(VI) system under low to medium concentrations of Fe(VI).
[0073] Example 6 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically investigating the applicability of a degradation system constructed by modified goethite and Fe(VI) to different anions in water, comprising the following steps: Take 100 mL of 10.0 μM sulfamethoxazole solution in a 250 mL conical flask, add sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate and sodium hydrogen phosphate respectively, so that the concentrations of chloride ions, sulfate ions, nitrate ions, bicarbonate ions and hydrogen phosphate ions in the solution are 5 mmol / L and 200 mmol / L, and no pH buffer solution is added. At the same time, the modified goethite and potassium ferrate (Fe(VI)) prepared by calcining goethite doped with 1% metal cobalt as a raw material at 200°C in Example 1 are added to initiate an oxidative degradation reaction, wherein the dosages of the modified goethite and Fe(VI) in the reaction system are 0.2 g / L and 0.2 mmol / L respectively, and the reaction is carried out in a water bath shaker at a speed of 150 rpm, a temperature of 30°C, and a reaction time of 150 min to complete the degradation of sulfamethoxazole in the water body.
[0074] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Fig.12 shown. Fig.12 In the above, Fe(VI) refers to a degradation system constructed by potassium permanganate alone; Co-FeOOH / Fe(VI) refers to a degradation system constructed by modified goethite prepared by calcining goethite doped with 1% cobalt as a raw material at 200°C and potassium permanganate.
[0075] Fig.12 This is a diagram showing the degradation effect of sulfamethoxazole in water by the system constructed by modified goethite and Fe(VI) in Example 6 of the present invention under different anion conditions. Fig.12It can be seen that after the introduction of 5 mM chloride ions, sulfate ions, nitrate ions, bicarbonate ions and hydrogen phosphate ions in the Co-FeOOH / Fe(VI) system, the degradation rates of sulfamethoxazole reached 39.09%, 50.68%, 42.15%, 78.19% and 91.85%, respectively. When the above five ions were added to the Co-FeOOH / Fe(VI) system at a concentration of 200 mM, the degradation rates of sulfamethoxazole increased to 68.03%, 79.35%, 80.92%, 100% and 73.92%, respectively. In the Fe(VI) system, when 5 mM chloride ions, sulfate ions, nitrate ions, bicarbonate ions and hydrogen phosphate ions were added, the degradation rates of sulfamethoxazole reached 11.94%, 15.06%, 12.91%, 49.77% and 75.63%, respectively. Compared with the blank control group of the Fe(VI) system without any additional ions (degradation rate of 16.24%), it was found that the introduction of chloride ions, sulfate ions and nitrate ions reduced the degradation rate by 4.3%, 1.18% and 3.33%, respectively; while the addition of bicarbonate ions and hydrogen phosphate ions significantly increased the degradation rate, with an increase of 33.53% and 59.39%, respectively. When the ion concentration added to the Fe(VI) system was increased to 200 mM, the degradation rates of sulfamethoxazole corresponding to chloride ions, sulfate ions, nitrate ions, bicarbonate ions and hydrogen phosphate ions were 36.11%, 39.19%, 31.95%, 100% and 48.94%, respectively. Compared with the blank control group of the Fe(VI) system without any additional ions, the addition of ions at this concentration level showed an enhancement of the degradation rate, with specific increases of 19.87%, 22.95%, 15.7%, 83.76% and 32.69%. It can be concluded that under certain experimental conditions, the performance of the Co-FeOOH / Fe(VI) system is better than that of the simple Fe(VI) system. Whether 5 mM or 200 mM of inorganic anions are added, the degradation of sulfamethoxazole in the Co-FeOOH / Fe(VI) system is positively affected. However, for the Fe(VI) system, a small number of ions at a specific concentration may bring negative effects. Therefore, in the present invention, when modified goethite is used to enhance the degradation performance of ferrate, it has excellent anti-interference ability. At the same time, the presence of an appropriate amount of inorganic anions in the system can be used as an effective means to regulate the advanced oxidation process of potassium ferrate to enhance the degradation ability of organic pollutants.
[0076] Example 7 A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, specifically investigating the applicability of a degradation system constructed by modified goethite and Fe(VI) under different initial pH conditions, comprising the following steps: 100 mL of a 10.0 μM sulfamethoxazole solution was taken into a 250 mL conical flask, and dilute sulfuric acid or sodium hydroxide was used to control the pH of the solution to 3.0, 5.0, 7.0, 9.0 and 11.0, respectively. At the same time, modified goethite and potassium ferrate (Fe(VI)) prepared by calcining goethite doped with metal cobalt at a doping ratio of 1% as a raw material at 200°C in Example 1 were added to initiate an oxidative degradation reaction, wherein the dosages of modified goethite and Fe(VI) in the reaction system were 0.2 g / L and 0.2 mmol / L, respectively. The reaction was carried out in a water bath shaker at a rotation speed of 150 rpm, a temperature of 30°C, and a reaction time of 150 min to complete the degradation of sulfamethoxazole in the water.
[0077] In this example, before high performance liquid chromatography analysis, 1.0 mL of sample was drawn at specified time intervals, filtered with a 0.45 μm filter, and quenched by adding 15 μL of a 1.0 mol / L sodium thiosulfate solution. The concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Fig.13 shown.
[0078] Fig.13 The degradation effect diagram of sulfamethoxazole in water under different pH conditions by the degradation system constructed by modified goethite and Fe(VI) in Example 7 of the present invention. Fig.13 It can be seen that when the initial pH values of the reaction system are 3, 5, 9 and 11, the degradation rates of sulfamethoxazole by the Co-FeOOH / Fe(VI) system are 52.8%, 31.16%, 30.47% and 28.58%, respectively. The corresponding degradation rates of the Fe(VI) system are 41.28%, 19.22%, 18.14% and 16.68%, respectively. In particular, when the initial pH value is 3, the degradation rate is significantly improved compared with the blank control group, indicating that the acidic environment helps to improve the degradation efficiency of sulfamethoxazole. In addition, under all tested pH conditions, the Co-FeOOH / Fe(VI) system exhibits a higher sulfamethoxazole degradation rate than the Fe(VI) system, which reasonably infers that the sulfamethoxazole degradation rate of the Co-FeOOH / Fe(VI) system is also better than that of the Fe(VI) system.
[0079] It can be seen from the above results that, compared with the conventional method, in the method of the present invention using modified goethite to enhance the degradation of organic pollutants in water bodies by ferrate, ferrate is activated by modified goethite having abundant oxygen vacancies and surface active Fe(II) sites, which can promote ferrate to quickly produce a large number of highly active species, thereby being able to construct a catalytic degradation system based on high-valent metals, and can achieve efficient degradation of organic pollutants in water bodies with less ferrate usage. It has the advantages of strong degradation selectivity, high degradation efficiency, good removal effect, small amount of catalyst and oxidant usage, no secondary pollution, etc., can efficiently remove a variety of organic pollutants in water bodies, has high use value, and good application prospects.
[0080] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for utilizing modified goethite to enhance ferrate degradation of organic pollutants in water, characterized in that: The method comprises adding modified goethite into a degradation system constructed by ferrate to degrade organic pollutants in water; the modified goethite is prepared by calcining metal-doped goethite as a raw material; and the doped metal in the metal-doped goethite is cobalt and / or copper.
2. The method according to claim 1, characterized in that The preparation method of the modified goethite comprises the following steps: S1, mixing a doped metal salt with an iron salt to react to obtain metal-doped goethite; S2. calcining the metal-doped goethite obtained in step S1 to obtain modified goethite.
3. The method according to claim 2, characterized in that In step S1, the mass of the doped metal salt is 0.1% to 5% of the mass of the iron salt; the doped metal salt is cobalt nitrate and / or copper nitrate; and the iron salt is iron nitrate.
4. The method according to claim 3, characterized in that In step S1, the mass of the doped metal salt is 0.8% to 5% of the mass of the iron salt.
5. The method according to claim 2, characterized in that The calcination is carried out under a reducing atmosphere; the reducing atmosphere is hydrogen or a mixed atmosphere of hydrogen and argon; the volume fraction of hydrogen in the mixed atmosphere is 5% to 15%; the calcination temperature is 150° C. to 250° C.; and the calcination time is 2h to 4h.
6. The method according to claim 5, characterized in that The calcination temperature is 180°C to 220°C.
7. The method according to any one of claims 1 to 6, characterized in that: Modified goethite is added to the degradation system constructed by ferrate to degrade organic pollutants in water, including the following steps: modified goethite, ferrate and organic pollutant wastewater are mixed to carry out oxidative degradation reaction to complete the degradation of organic pollutants in the wastewater.
8. The method according to claim 7, characterized in that The amount of modified goethite added is 0.1 g to 0.5 g per liter of the organic pollutant wastewater; the amount of ferrate added is 0.05 mmol to 0.5 mmol per liter of the organic pollutant wastewater.
9. The method according to claim 8, characterized in that The organic pollutants in the organic pollutant wastewater are at least one of 2,4-dichlorophenol, sulfamethoxazole, oxytetracycline, tetracycline, phenol and bisphenol A; the initial concentration of the organic pollutants in the organic pollutant wastewater is 10 μmol / L to 30 μmol / L; inorganic anions are also added to the organic pollutant wastewater.
10. The method according to claim 8, characterized in that The oxidative degradation reaction process also includes: adding borax-boric acid buffer solution to control the initial pH value of the system to 9.0±0.1; the pH value of the borax-boric acid buffer solution is 9.0; the temperature of the oxidative degradation reaction is 20°C to 40°C, and the oxidative degradation reaction is carried out under stirring conditions; the stirring speed is 100 rpm to 200 rpm; and the time of the oxidative degradation reaction is 30 min to 150 min.
Citation Information
Patent Citations
Cobalt isomorphic substituted goethite and application thereof in singlet oxygen dominated peroxymonosulfate catalytic system
CN114849709A
ZnO-MoO3 material loaded with oxygen vacancies, preparation method of ZnO-MoO3 material and application of ZnO-MoO3 material in activating ferrate to degrade water pollutants
CN117582975A
Shale gas fracturing flow-back fluid up-to-standard discharge pretreatment method and system
CN118579947A
Cited By
Method for promoting As oxidation by activating goethite through antibiotic drug molecules
CN120586340A
Method for promoting as oxidation by antibiotic drug molecules activated goethite
CN120586340B